Research advances of protein N-glycosylation’s biological functions and analytical methods and its role in kidney disease - 任伟夫; 边琪 (Linchuang shenzangbing zazhi)
As one of the most important post-translational modifications, glycosylation plays a significant role in the functions of proteins.N-glycosylation exerts critical effects in different biological processes among various forms of glycosylation, whereas aberrant glycosylation leads to multiple organ system dysfunction, such as congenital disorders of glycosylation or immune disease.Advanced mass spectrometry has been widely applied for uncovering the role of N-glycosylation in clinical practices and scientific researches.This reviews summarized synthetic processes, biological roles and mass-spectrometry-based analytical methods of N-glycosylation and focused upon the latest findings of N-glycosylation in renal physiology and nephropathy.